2009
DOI: 10.1016/j.comnet.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Remote detection of bottleneck links using spectral and statistical methods

Abstract: Persistently saturated links are abnormal conditions that indicate bottlenecks in Internet traffic. Network operators are interested in detecting such links for troubleshooting, to improve capacity planning and traffic estimation, and to detect denial-of-service attacks. Currently bottleneck links can be detected either locally, through SNMP information, or remotely, through active probing or passive flow-based analysis. However, local SNMP information may not be available due to administrative restrictions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…They find that the method is able to detect different attacks in a few seconds. It is also identified that bit-rate SNR is more effective to detect network traffic anomalies as compared to earlier proposed packet SNR in [80]. They evaluate both metrics through bPDM and conclude that bit-rate SNR is better in terms of detection time.…”
Section: Defense Against Application Layer Ddos Attacksmentioning
confidence: 90%
“…They find that the method is able to detect different attacks in a few seconds. It is also identified that bit-rate SNR is more effective to detect network traffic anomalies as compared to earlier proposed packet SNR in [80]. They evaluate both metrics through bPDM and conclude that bit-rate SNR is better in terms of detection time.…”
Section: Defense Against Application Layer Ddos Attacksmentioning
confidence: 90%
“…Spectral techniques have been employed to identify bottleneck links [7], [8] and routing information [15] as well as a range of network anomalies [1], [12]. Magnaghi et al detect anomalies within TCP flows using a wavelet-based approach to identify network misconfigurations [12].…”
Section: Related Workmentioning
confidence: 99%
“…We propose the parametric Modeled Attack Detector (MAD) based on time-series data and modify the method of He et al [7] to a sequential version, the Periodic Attack Detector (PAD), using spectrally-based techniques [4], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…We refer readers to the work by He et al [7] for an exposition on spectral detection methods. The contributions of this paper are therefore to develop the new MAD detection scheme and sequentialize the scheme in [7]; these methods operate on aggregate traffic streams and we quantify their effectivness on both controlled synthetic traffic and real traces captured in the wild.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation